P–381 Deciphering the genetic cause of recurrent and sporadic pregnancy loss. (6th August 2021) - Essers, R; Acharya, G; Al-Nasiry, S; Brunner, H; Deligiannis, S P; Fonova, E A; Kurg, A; Lebedev, I N; Macville, M V E; Nikitina, T V; Salumets, A; Sazhenova, E A; et al.
Abstract: Study question: To investigate the prevalence and effect of (mosaic) de novo genomic aberrations in recurrent pregnancy loss (RPL) and sporadic abortion (SA). Summary answer: Prevalence of maternal uniparental disomies (UPDs) was high in both cohorts. While chromosomal UPDs were found in both cohorts, genome wide UPDs were RPL specific. What is known already: Spontaneous abortion occurs in 10–15% of clinically recognized pregnancies and recurrent pregnancy loss in 1–3%. SA and RPL are associated with reduced quality of life. Multiple factors contribute to SA and RPL, such as uterine malformations and parental/fetal chromosomal abnormalities. However, in ∼60% of SA and RPL the cause remains unknown. UPD is defined as the presence of two homologues chromosomes originating from a single parent. This phenomenon can lead to imprinting disorders that are characterised by clinical features affecting growth, development and metabolism in liveborn offspring. However, it could also be responsible for pregnancy loss. Study design, size, duration: We recruited 32 families with pregnancy loss (n = 16 RPL cohort, n = 16 SA cohort) with no known genetic predispositions and normal karyotyping results in both parents and the fetus. Average maternal age was 28.68 years (SD = 5.43), paternal age 30.3 years (SD = 5.53), and the gestational age at pregnancy loss was 8.65 weeks (SD = 2.47). The average number of miscarriages in the RPL group was 3.57 (SD = 0.84). We profiled the genomic landscape of both cohorts using SNP typing. Participants/materials, setting, methods: We isolated DNA from blood of both parents and the placental tissues from the miscarried products of conception. The placenta tissues were sampled from two distinct extraembryonic and embryonic germ layers, the extraembryonic mesoderm and the chorionic villi cytotrophoblast. Subsequently, we performed SNP-genotyping using Illumina's Global-Screening Array–24 v2.0 BeadChips and applied haplarithmisis to delineate allelic architecture of fetal tissues of both cohorts. This allowed us to detect large de novo copy-number and -neutral (>10kb) changes. Main results and the role of chance: In this pilot study, we have analyzed 132 DNA samples (n = 32 families), of which 16 families were in the RPL cohort and 16 in the SA cohort. Within the RPL cohort, we found: one family with mosaic genome wide hexaploidy both in the extraembryonic mesoderm and chorionic villi, one family with a non-mosaic genome wide hetero UPD of the chorionic villi tissue, one family with a mosaic UPD of chromosome 14 in both tissues and tetraploidy exclusively in the chorionic villi, one family with a mosaic UPD of chromosome 16 in both tissues, one family with a mosaic UPD of chromosome 6 in both tissues, and another family with a mosaic UPD of chromosome 5 in the extraembryonic mesoderm. Within the SA group, one family showed a UPD of chromosome 7 and another family showed a segmental UPD of chromosome 5 in both tissues. Strikingly, all the UPDs found in this study were maternal in origin. Limitations, reasons for caution: The main limitation of this study is the resolution of detecting copy-neutral and copy-number variations, which is an inherent limiting factor of SNP-array technology. In addition, in the sample in which we observed non-mosaic genome wide UPD, maternal contamination is likely that can be investigated by other technologies. Wider implications of the findings: Multiple genome wide UPDs are found in the RPL group but none in the SA group, indicating an association between genome wide mosaic UPD and RPL. These findings could lead to a better understanding of causative factors for SA and RPL and the need for a SNP-based non-invasive prenatal testing. Trial registration number: Not applicable